Dental erosive potential of non-nutritive sweeteners (Aspartame, Acesulfame-k, Sucralose), and steviol glycosides in carbonated drinks / Mukarramah Zainal … [et al.] - Zainal, Mukarramah; Muhammad Adib, Abdul Halim; Nur Aqilah, Mohammad Zainan; Zulkapli, Rahayu (2019)
The link of acidic beverage consumption and dental erosion is a well-known fact. However, the substitution of sucrose and high-fructose corn syrup (HFCS) by either non-nutritive sweeteners (NNS) or Steviol Glycosides (SG) in carbonated soft drinks remains unclear. Objective: To assesses the dental erosion potential related to NNS (Aspartame, Acesulfame-K, Sucralose), and SG in carbonated soft drinks on 60 extracted healthy premolar teeth. Methods: Samples were randomly distributed into five groups: Group I: Classic Coke™, Group II: Light Coke™, Group III: Stevia Coke™, Group IV: Mineral Water, Group V: Distilled Water. Initially, pH, titratable acidity and calcium content of each tested drinks were determined. Standardize enamel surface area of premolar teeth were exposed in selected five beverages in 5-minute duration, three times in 4 hours interval daily for four consecutive days. The erosive potential was evaluated by measuring calcium released and teeth weight loss. Results: All tested carbonated soft drinks showed significance differences p<0.05. Light Coke™ showed the highest dental erosion followed by Classic Coke™ and Stevia Coke™. Conclusion: Substitution of sweeteners types in acidic beverages do give a different influence on teeth erosion. SG can be proposed as future sweetener substitute in acidic beverages to reduce dental erosion.